Tablets na educação infantil: tecnologia em sala de aula e seus benefícios para o processo de alfabetização - Machado, Ana Margarida Chiavaro (Universidade do Vale do Rio dos Sinos, 2014)
This research have the main objective to promote literacy through the process of insertion of mobile technology in early childhood education. It constitutes a qualitative and quantitative study, based on classroom observation and testings with students in Level B at Colegio Israelita Brasileiro, Porto Alegre / RS. Data collection started in 2011, and it was possible to observe the students development about literacy. This monitoring continue in 2012, in a accomplished pilot work with tablet, in 2013, followed by some initiatives using technologies, and finished in 2014, with an effective work for the inclusion of this technology in the school. Theorists like Fortuna (2001), Kishimoto (2001), Huizinga (2004), Amante (2011), Tapscott (2010), Huizinga (2004), Levy (1999), Ferreiro (1999), Vygotskty (1991), support the basis of the presented statements about playful, educationals technologies and literacy. The analysis of data from field diaries and student assessment revealed that the inclusion of tablet in the classroom can favor the literacy process of 5-6 year-old students and also expand the play situation and also contact with the literate environment. We perceived the technology as a strong ally of the teacher in structuring innovative and effective strategies in learning the written language.
Keywords: Tecnologia educacional; Tablet na sala de aula; Alfabetização; Lúdico; Educação Infantil; Acompanhamento de processos pedagógicos; Educational technology; Tablet in the classroom; Literacy; Playful; Early childhood education; Monitoring pedagogical processes; ACCNPQ::Ciências Humanas::Educação